The frontal aslant tract (FAT) and its role in speech, language and executive function. (February 2019) - Dick, Anthony Steven; Garic, Dea; Graziano, Paulo; Tremblay, Pascale
Abstract: In this review, we examine the structural connectivity of a recently-identified fiber pathway, the frontal aslant tract (FAT), and explore its function. We first review structural connectivity studies using tract-tracing methods in non-human primates, and diffusion-weighted imaging and electrostimulation in humans. These studies suggest a monosynaptic connection exists between the lateral inferior frontal gyrus and the pre-supplementary and supplementary motor areas of the medial superior frontal gyrus. This connection is termed the FAT. We then review research on the left FAT's putative role in supporting speech and language function, with particular focus on speech initiation, stuttering and verbal fluency. Next, we review research on the right FAT's putative role supporting executive function, namely inhibitory control and conflict monitoring for action. We summarize the extant body of empirical work by suggesting that the FAT plays a domain general role in the planning, timing, and coordination of sequential motor movements through the resolution of competition among potential motor plans. However, we also propose some domain specialization across the hemispheres. On the left hemisphere, the circuit is proposed to be specialized for speech actions. On the right hemisphere, the circuit is proposed to be specialized for general action control of the organism, especially in the visuo-spatial domain. We close the review with a discussion of the clinical significance of the FAT, and suggestions for further research on the pathway.